Identification of lncRNA and weighted gene coexpression network analysis of germinating Rhizopus delemar causing mucormycosis - Barsha Kalita; Abhijeet Roy; Aiswarya Jayaprakash; Annamalai Arunachalam; Lakshmi P.T.V (Mycology, 2023)
ABSTRACTRhizopus delemar, an opportunistic fungal pathogen, causes a highly fatal disease, mucormycosis. Spore germination is a crucial mechanism for disease pathogenesis. Thus, exploring the molecular mechanisms of fungal germination would underpin our knowledge of such transformation and, in turn, help control mucormycosis. To gain insight into the developmental process particularly associated with cell wall modification and synthesis, weighted gene co-expression network analysis (WGCNA) was performed including both coding and non-coding transcripts identified in the current study, to find out the module of interest in the germination stages. The module-trait relationship identified a particular module to have a high correlation only at the resting phase and further analysis revealed the module to be enriched for protein phosphorylation, carbohydrate metabolic process, and cellular response to stimulus. Moreover, co-expression network analysis of highly connected nodes revealed cell wall modifying enzymes, especially those involved in mannosylation, chitin-glucan crosslinking, and polygalacturonase activities co-expressing and interacting with the novel lncRNAs among which some of them predicted to be endogenous target mimic (eTM) lncRNAs. Hence, the present study provides an insight into the onset of spore germination and the information on the novel non-coding transcripts with key cell wall–related enzymes as potential targets against mucormycosis.